Supervision Management of Madrasah Heads in Improving Teacher Performance in Tangerang Regency - Bakri; Ulfiah; Ujang Nurjaman; Rita Sulastini (Yayasan Azka Hafidz Maulana, 2022)
The existence of madrasah principles in educational institutions has a very important role in developing and leading educational institutions, because madrasah principals are one of the keys to the success of quality educational institutions in the process and output, therefore the madrasah principal as a supervisor is expected to provide positive values ​​(motivation) , fostering, and developing teacher competencies) towards improving the performance of madrasa teachers. This study reveals the implementation of academic supervision management in improving teacher performance at MA Daarul Muttaqien and MAN 3 Tangerang. This type of research is qualitative research, data sources are primary data and secondary data, data collection techniques through observation, interviews (interviews), and documentation. research instruments, namely, observation guides, interview guidelines and documentation references, data processing and analysis techniques, namely deductive analysis, comparative analysis, data verification, namely drawing conclusions on the data that has been presented, testing the validity of the data, namely triangulation tests, and conducting checks. The results of the research findings indicate that: 1) the planning of the madrasah principal's academic supervision program is arranged in accordance with the rules. 2) the ability of the principal has optimized the implementation of academic supervision and the implementation of the academic supervision of the madrasah principal. 3) the activities of the evaluation process by the principal of the madrasa to the teacher are carried out by observing the teacher in class learning activities. 4) The implementation of academic supervision has a real impact on improving the performance of madrasa teachers, namely teachers.